Deconstructing Circadian Rhythmicity with Models and Manipulations. Issue 6 (June 2016) - Pauls, Scott D.; Honma, Ken-Ichi; Honma, Sato; Silver, Rae
Abstract : A master brain clock, localized to the hypothalamic suprachiasmatic nucleus (SCN), coordinates daily rhythms of physiology and behavior. Within the SCN, interconnected individual neurons are oscillators that, as an ensemble, function to send a coherent timing signal to the brain and body. However, individually, these neurons display different amplitudes, periods, and phases of oscillation. The dynamic properties of the SCN have been characterized over several spatial levels of analysis, from proteins to cells to tissues, and over several temporal ranges, from milliseconds to weeks. Modeling tools guide empirical research in this complex and multiscale spatiotemporal environment. Given that the SCN is a prototypical example of oscillating neural systems, principles of its organization hold promise as general prototypes of rhythms in other frequencies. Trends: The SCN generates a master circadian rhythm via the coordination of a heterogeneous group of oscillatory neurons. Researchers have studied dynamics over several spatial and temporal scales, informed by, and informing, mathematical models of components of the function of the SCN. Emerging techniques enable the observation of multiple systems within the SCN simultaneously, showing directly how different subprocesses in the formation and maintenance of the circadian rhythm interact. Multiplex network models of interacting processes, informed by these new observations, will provide new insights into circadian organization and guide new experimentation. Given that the SCN serves as a canonical example of an oscillating neural system, these models will likely form prototypes for general models applicable to other oscillatory systems.